Controladoria como apoio à governança corporativa: estudo de caso em uma cooperativa agropecuária - Schaffer, Gisela (Universidade do Vale do Rio dos Sinos, 2013)
International financial scandals have generated a rise in corporative governance-based scientific studies inside open capital companies. Even non-obligated organizations have also using good practices in corporative governance. Thus, this research analyses how corporative governance and its milestones principles, with controllership and Business Intelligence techniques, can be structured. Research took place in a southern Brazilian co-op agribusiness, mainly focused in dairy processing from milk collected from partners and members. The research kick-off was made from data collection from questionnaires to company management and interviews with director’s board, vice-president, CEO, CFO and IT manager. After, the questions had been classified by corporative governance’s milestones, and confirmed by a PhD’s board, thus allowing crossing of good practices issues with administration board, audit committee, management, members’ general meeting and external auditors. Disclosure, accountability and compliance were the milestones analyzed. A second crossing was made using good practices supported by controllership, considering ranked-based issues as identified by the questionnaires and interviews. Based on this last data crossing, relevant information was classified to bond with Business Intelligence techniques. This related data showed a controllership and Business Intelligence support for corporative governance, considering disclosure, accountability and compliance.
Keywords: Governança corporativa; Controladoria; Cooperativa e business intelligence; Corporate governance; Management accounting; Cooperative and business intelligence; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis